The Relationship of Avian Influenza and Waterbirds in Creating Genetic Diversity and the Role of Waterbirds as Reservoir for Avian Influenza - Dyah Ayu Hewajuli; Ni Luh Putu Indi Dharmayanti (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2012)
Outbreaks of Avian Influenza (AI) has enormous implications for poultry and human health.These outbreaks are caused by influenza A virus that belongS to the family of Orthomyxoviridae. These viruses are RNA viruses, negative polarity, and the envelope has segmented genom. Generally, Avian Influenza is a disease which originally occurred in birds with complex ecology including reassortment and transmission among different species of birds and mammals. The gene of AI virus can be transmitted among human and avian species as shown by the virus reasortantment that caused pandemic human influenza in 1957 and 1968. Pandemi in 1957 and 1968 were different from previously human viruses because the substitution of several genes are derived from avian viruses. Wild waterfowls especially Anseriformes (duck, muscovy duck and geese) and Charadriiformes (gulls, seabirds, wild birds) are the natural reservoirs for influenza type A viruses and play important role on the ecology and propagation of the virus. From this reservoir, influenza type A virus usually can be transmitted to other birds, mammals (including human) and caused outbreak of lethal diseases. Waterfowl that is infected with influenza A virus usually does not show any clinical symptoms. However, several reports stated that HPAI viruses can cause severe disease with neurogical disorders led to death in waterfowl. Migration of birds including waterfowls have active role in transmitting and spreading the disease. Movement of wild birds and inappropriate poultry trade transportation play a greater role as vector in spreading HPAI to humans. Ecological change of environment has also a great effect in spreading AI viruses. The spreading pattern of AI viruses is usually influenced by seasons, where the prevalence of AI was reported to be in the fall, winter and rainy seasons. Finally, the effective control strategies against the spreading of AI viruses is required. Programs of monitoring, surveilence and vaccination is part of the control strategies of AI viruse spreading besides other strategies that had been applied. Key words: Avian Influenza, reservoir of AI, waterbirds, migration